2023
DOI: 10.1177/15459683231170539
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neurofeedback on Cognitive Function, Productive Activity, and Quality of Life in Patients With Traumatic Brain Injury: A Randomized Controlled Trial

Abstract: Background Cognitive impairment is common in patients with traumatic brain injury (TBI). Studies that have examined the effectiveness of neurofeedback (NFB) on cognitive function following TBI have had poor study designs and small sample sizes. Objectives This randomized controlled trial assessed the effects of low-resolution tomography Z-score NFB (LZNFB) and theta/beta NFB on cognitive impairment, return to productive activity, and quality of life in patients with TBI. Methods We randomly assigned 87 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The following were coded: theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which includes both the sensory-motor rhythm (12-15 Hz or 12-18 Hz), and gamma (30-100 Hz).…”
Section: Eeg Band Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following were coded: theta (4-8 Hz), alpha (8-12 Hz), beta (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), which includes both the sensory-motor rhythm (12-15 Hz or 12-18 Hz), and gamma (30-100 Hz).…”
Section: Eeg Band Definitionmentioning
confidence: 99%
“…NFB has been applied to memory function in patients with MCI, and a positive effect on memory enhancement was reported [ 11 , 12 , 13 ]. A clinical trial reported a positive effect of theta-down NFB on learning memory and overall cognitive performance in patients with Alzheimer’s disease [ 14 ]. Several systemic reviews provided evidence of NFB in the elderly [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%